2013
DOI: 10.2478/nor-2013-0058
|View full text |Cite
|
Sign up to set email alerts
|

Ironic Crisis Communication?

Abstract: Humour and irony are normally not recommended within crisis communication. So when the main Swedish rail company SJ in January 2011 issued three short videos taking an ironical stance on the company and its damaged reputation, it attracted a great deal of attention. But the good will generated by this unexpected irony was apparently never fully understood by the management, and was thus lost or directly undermined by their subsequent communication. This article addresses the specific case of SJ’s crisis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…In such a case, humour reduces the perceived sincerity of the response. Previous case studies have shown that humour may be not applicable when a crisis situation is severe (see Kim et al., ; Vigsø, ) as a humorous crisis message may perceived as lacking concern and empathy for victims (Sorensen, ). We also found that when the public's assessment of the organization's sincerity is low, the burden of responsibility on the organization is higher, which confirms the findings of Claeys et al.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 4 more Smart Citations
“…In such a case, humour reduces the perceived sincerity of the response. Previous case studies have shown that humour may be not applicable when a crisis situation is severe (see Kim et al., ; Vigsø, ) as a humorous crisis message may perceived as lacking concern and empathy for victims (Sorensen, ). We also found that when the public's assessment of the organization's sincerity is low, the burden of responsibility on the organization is higher, which confirms the findings of Claeys et al.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Several case analyses of crises (e.g., Kim et al., ; Sellnow & Brand, ; Vigsø, ) suggest that public relations practitioners prefer to use self‐deprecating humour. This type of humour may be effective because it arouses the public's attention and expresses the organization's willingness to rectify the problem in a humorous way (Vigsø, ).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations